Pengembangan Perancangan Aplikas Pengembangan Perancangan Aplikasi Akademik Penjadwalan Mata Pelajaran Menggunakan Metode UML dan UCD (User Centered Design) - Sanjaya, M. Rudi; Ruskan, Endang Lestari; Putra, Bayu Wijaya; Ismail, Ahmad Arrijal; Maula, Nurly Izzatul (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
Abstract Technological from time to time are increasingly needed, especially in the world of education, where the world of education still uses conventional methods, this method can be replaced by computerized methods or it can be said that technology is in the form of applications, with applications it can make work in schools or Islamic boarding schools easier. What will be built is a website for scheduling subjects in schools or Islamic boarding schools. The aim of this research is to design, build and develop an academic application for scheduling subjects using the UCD (User Centered Design) method. The benefit of this research is that it makes it easier to manage integrated subject scheduling based on website, the research method uses interviews, observation and literature studies, then the design method uses the UML (Unified Modeling Language) method, then for evaluation uses the UCD (User Center Design) method, the results of validity testing from questions L1 to L 10 are found df = n-2 =28-2 =26, r calculated to get L1 is 0.639, L2 = 0.735, L3= 0.511, L4=0.753, L5=0.486, L6=0.822, L7 =0.471, L8= 0.868, L9=0.620 , and L10 = 0.834 where r calculated > r table obtained r table is 0.3172, that validity testing produces valid data, then the total value for reliability testing if the Cronbach's alpha value is > 0.70 is reliable, the total for reliability testing is 0.908, meaning the data is reliable. Keywords—UCD, UML, Validity and Reliability.